Meningkatkan Hasil Belajar Peserta Didik dengan Penerapan Model Problem Based Learning Melalui Pembelajaran Daring Terhadap Peserta Didik Kelas III SD Negeri Tlogomulyo - Khasanah, Uswatun (Prosiding University Research Colloquium, 2021)
The purpose of this research is to find out the level of achievement og learner’s learning outcomes in learning, as well as the ability of learner’s in applying learning materials in everyday life through online learning. The model used in this learning is the Problem Based Learning (PBL) model with the research subject of class III learner’s at Tlogomulyo Temanggung State Elementary School which numbered 17 learners. The result of the study obtained the percentage of learning outcomes of learner knowledge from cycle I to cycle II increased, reaching 17,65%, then the percentage of learning outcomes of learner’s attitude increased by 11,77%, then the percentage of learning outcomes of learner’s skills increased by 23,53%. The method in this research is a class action research method. The data collection in this study was using tests. The result showed that with the application of the Problem Based Learning (PBL) model can increase the learning outcomes of learners, it can be seen from many learners who become more active in asking questions during learning and begin to dare to express opinion.